TINJAUAN YURIDIS “PERJANJIAN PERCERAIAN” BERDASARKAN KITAB UNDANG-UNDANG HUKUM PERDATA DAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN (STUDI KASUS PERJANJIAN PERCERAIAN ANTARA MISNO-NY.EKO SARYUNINGTYAS DAN SUDARMAN SOH-DEWI) - KIKI ANNIVIA PRAVITA GUNADI (PREMISE LAW JURNAL, 2015)
Every human being has a desire to get married, only once and forever. However, maintaining a married life which unites two individuals with different personality and different interest is difficult; therefore, many marriages end with divorces. The divorce itself frequently causes new problem so that many people attempt to make “Divorce Contracts” in order to prevent from the problem. It can be concluded that the provision which clearly and specifically regulates “Divorce Contract” as a unity has not yet been found either in the Civil Code or in Law No. 1/1974 on Marriage. Therefore, the legal basis of “Divorce Contract” should be seen from two perspectives: from material perspective or the content of “Divorce Contract”; that is the right and obligation of husband and wife (Article 30, Article 31, Article 32, Article 33, and article 34 of Law No. 1/1974 on Marriage), and the impact of the end of marriage because of divorce (Article 4, paragraph 3, Article 41, point a and point b in conjunction with Article 45, Article 35 in conjunction with Article 37 and Article 36 of Law No. 1/1974 on Marriage), with definition on the transaction which is prohibited between husband and wife (Article 1467, Article 1601, Article 1678, Article 1910, and Article 1988 of the Civil Code), from the formal perspective or the form of “Divorce Contract”: Article 1320 of the Civil Code. Keywords: “Divorce Contract”, Divorce Consequence